1984
DOI: 10.1093/ptj/64.2.194
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Physical Conditioning on Self-Concept of Adult Obese Males

Abstract: The purpose of the study was to investigate possible psychological changes in obese men after participating in an eight-week nutrition and physical conditioning program. The subjects, 45 male, metropolitan policemen who were considered at least 20 percent over their optimum body weights, were placed on diets and received weekly instruction on topics of nutrition and exercise. The subjects were randomly divided into two groups, one that participated in aerobic conditioning and one that did not. The amount of ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Across the remaining multigroup studies with higher risk of bias ratings (in ≥7 items) the most commonly reported outcomes were fitness and weight. CVF increased by ~11% in a 10-week supervised aerobic exercise intervention (compared with ~1% improvement in an anaerobic training group and a ~0.8% deterioration in a control group)49, and by ~21% (compared with 13.4% in a control group)41 over 9 weeks, and by ~38% (compared with ~13% in an education only group)51 over 8 weeks of combined physical activity and diet interventions (structured activity plus education). The only other controlled trial that measured CVF did not find any improvement after 16 weeks of structured exercise only 50.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…Across the remaining multigroup studies with higher risk of bias ratings (in ≥7 items) the most commonly reported outcomes were fitness and weight. CVF increased by ~11% in a 10-week supervised aerobic exercise intervention (compared with ~1% improvement in an anaerobic training group and a ~0.8% deterioration in a control group)49, and by ~21% (compared with 13.4% in a control group)41 over 9 weeks, and by ~38% (compared with ~13% in an education only group)51 over 8 weeks of combined physical activity and diet interventions (structured activity plus education). The only other controlled trial that measured CVF did not find any improvement after 16 weeks of structured exercise only 50.…”
Section: Resultsmentioning
confidence: 96%
“…Follow-up duration ranged from 8 weeks51 to 6 years31–33 following intervention (duration of ≤6 months, n=18 studies;36–46 48–55 18 months, n=1 study;47 24 months, n=1 study34 35 and 6 years, n=131–33 study).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…12-17 It is known that an exercise experience can influence exercise-related self-efficacy, performance, beliefs in benefit, and perceptions of barriers. [16][17][18][19] Consequently, personal experience with a behavior could change attitudes and beliefs from those held when the person was naive to the experience, and affect subsequent decisions.…”
Section: Introductionmentioning
confidence: 99%